PENGARUH KOMUNIKASI DAN MOTIVASI BERPRESTASI TERHADAP KEPUASAN PELANGGAN di PPs UNJ - Desi Rahmawati (Jurnal Manajemen Pendidikan, 2010)
The objective of this causal research is to obtain information concerning the effect of communication and achievement motivation on PPs UNJ student satisfaction. The research was conducted by using a survey method with path analysis in testing hypothesis. In this research, PPs UNJ students of the school year 2009/2010 has been choosen as a unit analysis and 211 samples of student were selected in random. The results of the research are as follows: (1) there is a direct positive effect of communication on achievement motivation indicated by the value of the path coefficient = 0.404; (2) there is a direct positive effect of communication on PPs UNJ student satisfaction indicated by the value of the path coefficient = 0,223; (3) there is a direct positive effect of achievement motivation on PPs UNJ student satisfaction indicated by the value of the path coefficient = 0,304. Therefore, student satisfaction can be improved by optimizing the communication made by the director and staff, lecturers and administrative staff to students using a variety of appropriate media to get positive feedback from students. Furthermore, by constantly increasing the motivation of the students themselves.